Pentingnya Kode Etik dalam Mengembangkan Profesionalisme Guru - Dorlan Naibaho; Rostiar (JOURNAL SAINS STUDENT RESEARCH, 2025)
The teacher's task is to advance education, which will have an impact on the development and progress of the Indonesian state. Teachers adhere to a code of ethics to uphold their dignity and professionalism in the workplace. However, many teachers are unable to do their jobs professionally, which can be detrimental to many people. Using a literature review research approach, the author attempts to demonstrate the significance of comprehending and adhering to a code of ethics in order to enhance teacher professionalism. The research results show that implementing a teacher code of ethics improves teacher professionalism, educational quality and student learning outcomes. Education, supervision, organizational culture, and school leadership are factors that influence the implementation of a teacher code of ethics.